2009
DOI: 10.1016/j.molcel.2008.12.020
|View full text |Cite
|
Sign up to set email alerts
|

βTrCP- and Rsk1/2-Mediated Degradation of BimEL Inhibits Apoptosis

Abstract: Summary The BimEL tumor suppressor is a potent pro-apoptotic BH3-only protein. We found that in response to survival signals BimEL was rapidly phosphorylated on three serine residues in a conserved degron, facilitating binding and degradation via the F-box protein βTrCP. Phosphorylation of the BimEL degron was executed by Rsk1/2 and promoted by the Erk1/2-mediated phosphorylation of BimEL on Ser69. Compared to wild type BimEL, a BimEL phosphorylation mutant unable to bind βTrCP was stabilized and consequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
173
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 157 publications
(190 citation statements)
references
References 32 publications
13
173
1
1
Order By: Relevance
“…This mechanism of BimEL inactivation is similar to that observed after growth factor stimulation with the exception that the bTrCP phosphodegron is activated by Rsk1/2 downstream of growth factors rather than Aurora A. 20 We observed that the phosphorylation of S93/94/98 is dynamic and reversed by the activity of PP2A leading to the stabilization of BimEL proteins levels after Whole-cell extracts were analyzed by immunoblot to detect endogenous BimEL. P-T210 Plk1 and total Plk1 were used as controls to confirm the downstream effects of the aurora A inhibitor MLN8054.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…This mechanism of BimEL inactivation is similar to that observed after growth factor stimulation with the exception that the bTrCP phosphodegron is activated by Rsk1/2 downstream of growth factors rather than Aurora A. 20 We observed that the phosphorylation of S93/94/98 is dynamic and reversed by the activity of PP2A leading to the stabilization of BimEL proteins levels after Whole-cell extracts were analyzed by immunoblot to detect endogenous BimEL. P-T210 Plk1 and total Plk1 were used as controls to confirm the downstream effects of the aurora A inhibitor MLN8054.…”
Section: Discussionsupporting
confidence: 75%
“…BimEL has been shown to form complexes with kinases that phosphorylate it. 19,20,24 Similarly, in Figure 6g we show that that GST-BimEL was able to pull down Aurora A from mitotic extracts derived from HeLa or 293T cells.…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations